2016
DOI: 10.1159/000445564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitrification on Outcomes of In VivoMature, In Vitro-Mature and Immature Human Oocytes

Abstract: Key Words Vitrification • In vivo-mature human oocytes • In vitro-mature human oocytes • Immature human oocytesAbstract Background/Aims: To observe the effects of vitrification on spindle, zona pellucida, embryonic aneuploidy and DNA injury in in vivo-maruted, in vitro-mature and immature human oocytes. Methods: Between January 2009 and February 2015, 223 immature oocytes from 450 infertile patients, and 31 in vivo-mature oocytes from 3 infertile couples were collected. Of the 223 immature oocytes, 113 were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Song et al (106) were also using GV- and GVBD (MI)-stage oocytes generated from IVF cycles. Control was oocyte matured in vivo without vitrification and vitrification groups were where vitrification was performed before or after IVM of immature oocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Song et al (106) were also using GV- and GVBD (MI)-stage oocytes generated from IVF cycles. Control was oocyte matured in vivo without vitrification and vitrification groups were where vitrification was performed before or after IVM of immature oocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Although the cryopreservation technology for human oocytes has been enhanced and has achieved a high survival rate, it still cannot be routinely applied in clinical practice because of the poor developmental competence of oocytes after cryopreservation 11,12 . A previous study has shown that MLT acts as a protective agent that can promote oocyte development 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, although oocyte cryopreservation technology has been optimized and has achieved a high survival rate after cryopreservation, the blastocyst rate and the clinical pregnancy rate of cryopreserved oocytes are still lower than those of the fresh oocytes. Recent studies have shown that the blastocyst rate is 3.5%‐21.4% 10‐12 and the clinical pregnancy rate is 10.7% 13 of in vitro‐matured metaphase II (IVM‐MII) human oocytes after cryopreservation. Therefore, it is crucial to improve the quality of vitrified‐warmed oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study showed that an increase in the perivitelline gap as well as a thickening and hardening of the zona pellucida was observed in oocytes after vitrification freezing [ 35 ]. Also, reduced ATP content and inadequate mitochondrial energy can lead to impaired spindle assembly and decreased spindle density [ 36 , 37 ]. The stability of the MMP and calcium level is particularly important for the quality of the oocyte.…”
Section: Melatonin Benefits Vitrification Freezingmentioning
confidence: 99%
“…And these excess lipid peroxides produce excess MDA, which leads to DNA damage even apoptosis in oocytes [ 67 ]. Higher levels of oxidative stress may also lead to spindle disorders, organelle degeneration, cytoplasmic heterogeneity, and reduced mitochondrial function in oocytes [ 36 , 39 , 40 , 68 ]. And ultimately, it results in poorer fertilization rates, lower high-quality blastocyst rates, and worse clinical pregnancy outcomes in PCOS patients [ 69 ].…”
Section: Melatonin Improves the Dysregulation Of Oxidative Stress Homeostasis Associated With Pcosmentioning
confidence: 99%